The Effect of Service Quality and Trust on Repurchase Intentions, Mediated by Consumer Satisfaction in the Multifinance Industry - Cittadhi Astridewi Nirmala; Damelina Basauli Tambunan; Yuli Kartika Dewi (Journal Research of Social Science, Economics, and Management, 2026)
The automotive financing sector, particularly used car financing, plays a strategic role in Indonesia’s financial services industry. Amid increasingly intense competition among multifinance companies, retaining repeat customers has become a major challenge. This study aims to analyze the influence of service quality and trust on repurchase intention, with customer satisfaction acting as a mediating variable, among repeat financing customers at conventional multifinance companies. The study employed a quantitative associative approach using the PLS-SEM method with SmartPLS software. Data were collected from 100 purposively selected respondents who had completed at least one prior vehicle financing contract. The findings indicate that service quality does not significantly influence customer satisfaction or repurchase intention. In contrast, trust has a positive and significant effect on customer satisfaction, although its direct effect on repurchase intention is not statistically significant. Furthermore, customer satisfaction does not significantly mediate the relationship between service quality and repurchase intention, but it significantly mediates the relationship between trust and repurchase intention. These findings suggest that repeat financing customers in conventional multifinance companies tend to prioritize relational factors such as trust, transparency, and a sense of security rather than operational service quality alone. This study contributes to the service marketing and customer behavior literature by emphasizing the importance of relationship quality in shaping repeat financing behavior in the multifinance industry. Practically, the findings imply that multifinance companies should prioritize trust-building strategies and customer relationship management to strengthen long-term customer retention.